Sexual deviance and society a sociological examination - Worthen, Meredith G. F. (Routledge, 2016)
"In a society where sexualized media has become background noise, we are　frequently discouraged from frank and　open discussions about sex and　offered few tools for understanding sexual behaviors and sexualities that are perceived as being out of the norm. This book encourages readers to establish new ways of thinking about stigmatized peoples and behaviors, and to think critically about gender, sex, sexuality and sex crimes" -- Provided by publisher.